2016
DOI: 10.1109/tci.2016.2523427
|View full text |Cite
|
Sign up to set email alerts
|

Joint Reconstruction of Absorbed Optical Energy Density and Sound Speed Distributions in Photoacoustic Computed Tomography: A Numerical Investigation

Abstract: Photoacoustic computed tomography (PACT) is a rapidly emerging bioimaging modality that seeks to reconstruct an estimate of the absorbed optical energy density within an object. Conventional PACT image reconstruction methods assume a constant speed-of-sound (SOS), which can result in image artifacts when acoustic aberrations are significant. It has been demonstrated that incorporating knowledge of an object’s SOS distribution into a PACT image reconstruction method can improve image quality. However, in many c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…This is consistent with previous Note: μ a , optical absorption coefficient; μ s , optical scattering coefficient; g, scattering anisotropy; n, refractive index. studies [7][8][9][10]12 that have demonstrated that consideration of the acoustic properties of the medium is necessary for accurate PACT image reconstruction.…”
Section: Pact Simulation Employing the Generated Phantomsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous Note: μ a , optical absorption coefficient; μ s , optical scattering coefficient; g, scattering anisotropy; n, refractive index. studies [7][8][9][10]12 that have demonstrated that consideration of the acoustic properties of the medium is necessary for accurate PACT image reconstruction.…”
Section: Pact Simulation Employing the Generated Phantomsmentioning
confidence: 99%
“…Both PACT and USCT are radiation-free, breast-compressionfree, and relatively inexpensive. In addition, the integration of PACT and USCT has drawn increasing attention [7][8][9][10][11] because they provide complementary contrasts, the speed of sound information produced by USCT can improve the accuracy of PACT image reconstruction, and the two imaging modalities can share a common ultrasonic detection system. These advantages make PACT and USCT promising tools for breast cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the SOS distribution is typically unknown. Further, it has been shown that, in general, the SOS and initial pressure distributions cannot both be stably recovered from PACT measurements alone [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…An estimate of the initial pressure distribution can be obtained by solving the penalized least-squares optimization problem [17, 22, 37], boldp^0=arg minp00thinmathspaceFpfalse(p0,boldcfalse)+λpfalse(p0false),where F p ( p 0 , c ) is a data fidelity term, ℛ p ( p 0 ) is a regularization function, and λ p is a regularization parameter, which controls the relative weight of the ℛ p ( p 0 ) term, Here, F p ( p 0 , c ) is given by Fpfalse(p0false)boldcfalse)12false‖boldgitalicpa¯MHpafalse(boldcfalse)p0false‖22,where boldgitalicpa¯NrecL is the measured data. For this problem, the data fidelity term is differentiable and convex with respect to p 0 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation